Pharmacokinetics of Cenobamate: Results From Single and Multiple Oral Ascending‐Dose Studies in Healthy Subjects - Vernillet, Laurent; Greene, Stephen A.; Kamin, Marc (Clinical pharmacology in drug development, 2020)
Cenobamate (YKP3089) is an antiepileptic drug recently approved by the Food and Drug Administration for the treatment of focal (partial‐onset) seizures in adults. The objectives of a first‐in‐human single‐ascending‐dose study and 3 multiple‐ascending‐dose studies were to characterize the pharmacokinetics, safety, and tolerability of cenobamate after single‐dose and multiple‐dose administration in healthy subjects. The 4 randomized, placebo‐controlled, double‐blind studies were conducted in 210 healthy subjects receiving single (5 to 750 mg) or multiple (50 to 600 mg/day) oral doses of cenobamate or placebo using capsule formulation. Safety assessments included treatment‐emergent adverse events (TEAEs) and laboratory evaluations. Maximum plasma concentrations of cenobamate were observed between 0.8 and 4.0 hours after oral administration. Cmax increased in a dose‐proportional manner for single‐ and multiple‐dose administration across all tested doses. Although the AUC of cenobamate increased in a more than dose‐proportional manner after single‐dose administration, a dose‐proportional increase in cenobamate AUCτ was observed after multiple dosing from 50 to 500 mg/day. Cenobamate exhibited low oral clearance (decreasing from approximately 1.4 to 0.50 L/h with dose increase) and long terminal half‐life (range, approximately 30 to 76 hours with increasing dose). Steady‐state was attained after approximately 2 weeks, and the accumulation ratio was approximately 5 over the 50 to 300 mg/day range. The pharmacokinetic characteristics of cenobamate are consistent with once‐daily dosing. Most TEAEs were mild in severity, 2 serious TEAEs were reported, and no deaths occurred across all studies. Except for multiple daily doses of 600 mg, all doses were generally well tolerated.